Standardization And Analytical Profiling Of A Selected Polyherbal Formulation For Osteoarthritis - Yadav, Garima; Nandal, Rimmy (Journal of Neonatal Surgery, 2025)
The present study focuses on the development and evaluation of a polyherbal formulation comprising Anethum graveolens, Cedrus deodara, Piper longum (fruit and stem), Embelia ribes, and Saindhava lavana, traditionally used in Ayurvedic medicine for their anti-inflammatory and analgesic properties. The formulation was subjected to detailed pharmacognostic and physicochemical assessments, including organoleptic evaluation, foreign organic matter analysis, ash values, extractive values, and fluorescence tests. Phytochemical screening confirmed the presence of significant levels of phenols and tannins. To evaluate the anti-arthritic efficacy, the formulation was tested using Complete Freund’s Adjuvant (CFA)-induced arthritis in Wistar rats. Key parameters such as paw volume, joint diameter, arthritic score, body weight, nociceptive and thermal hyperalgesia thresholds, hematological indices, and inflammatory biomarkers (CRP, RF, ALP, ALT, AST) were measured. The treated groups exhibited a significant reduction in inflammatory and arthritic symptoms compared to the arthritic control group, alongside normalization of hematological and biochemical markers. The results indicate a potent anti-arthritic effect, likely due to the synergistic action of the bioactive phytoconstituents present in the formulation. This study supports the therapeutic potential of the polyherbal formulation as a safe and effective alternative for managing rheumatoid arthritis and calls for further exploration in preclinical and clinical settings